Synthesis of Crop Protection Agent Mandipropamid (Indian Journal of Chemistry (IJC), 2023)
A simple synthesis of a novel fungicide Mandipropamid has been achieved in 6 steps, with an overall yield 43%. Synthesis started from commercially available starting materials, 4-chloroacetophenone and vanillin. The key steps involved in the synthesis are Cannizzaro and Henry reactions, amide bond formation and O-propargylation.